Post-conflict policekeeping: the response to the tensions and the role of the Participating Police Force (PPF) in the Regional Assistance Mission to the Solomon Islands (RAMSI) - Heyer, Garth den (Routledge international handbook of policing crises and emergencies, 2025)
From 1998 to 2003, the Solomon Islands experienced a devastating ethnic uprising that became known locally as ‘the tensions’. When fighting broke out in 1998 between the factions of the country’s two main islands, Guadalcanal and Malaita, the Solomon Islands was already one of the poorest nations in the Pacific. A fragile peace was reached with the signing of the Townsville Peace Agreement 2000. To consolidate the peace accord, the Solomon Islands prime minister requested assistance from Australia and New Zealand and from the South Pacific Leaders Forum. This request led to the establishment of the Participating Police Force (PPF), which was formed to lead the Regional Assistance Mission to the Solomon Islands (RAMSI). This chapter examines this unique, police-led, post-conflict peacekeeping role of the PPF.